A Analisis Kelayakan Battery 110 VDC Dalam Mengsuplai Pembebanan ( Studi Kasus Gardu Induk Perawang 150 kV ) : Feasibility Analysis of 110 VDC Battery in Supplying Loading (Case Study of 150 kV Perawang Substation) - nurhadi, irvan (Institut Riset dan Publikasi Indonesia, 2022)
The rectifier functions as a transformer from AC voltage to DC voltage. The problem generally lies in the AC voltage when entering the recifier, namely the occurrence of trip disturbances on the side of the self-use transformer (PS) at the substation which is usually caused by disturbances in the transmission line or disturbances in the power transformer. The purpose of this research is to determine the condition and feasibility the battery in the perawang substation. From the measurement of each cell on the 110 Vdc battery unit 1 month of February, it can be seen that the average charge voltage is 1.40V, when the average discharge voltage is 1.29 V. Then the unit 2 battery is in charge the average voltage is 1, 41 V while when the discharge state the average voltage is 1.29 V. Thus, according to PLN measurement standards a good and decent battery has a voltage of 1.30 V to 1.450 V when charged while a decent battery discharge has a voltage of 1.10 V up to 1.25 V, it is stated that the 110 Vdc battery at the Perawang Substation unit 1 and unit 2 are in decent condition. Based on the calculation results, it can be seen that the unit 1 load on the 110 Vdc substation battery is 770 watts, and the unit 2 load is 1540 watts.